Occurrence of enterotoxin genes and macrorestriction analysis of Staphylococcus aureus isolated from bovine mastitis and bulk-tank milk samples in Italy. An epidemiological study - Roberto Rosmini; Christoph Lämmler; Cosima Annemüller; Maria Cristina Fontana; Leonardo Alberghini; Andrea Serraino (Italian Journal of Animal Science, 2010)
The goal of the study was to genotypically compare S. aureus isolates from mastitis milk and raw milk to identify the relation between strains and to assess the enterotoxigenicity of the isolates. Eighty-three Staphylococcus aureus isolates recovered from cows and bulk tank milk of five farms in northern Italy were compared genotypically. The genes for the enterotoxins A, D, G and I, but not for B, C, E and H and the toxic shock syndrome toxin 1 (TSST-1), were detected by PCR amplification. Macrorestriction analysis with the restrictions enzyme SmaI revealed 14 pulsed-field gel electrophoresis patterns. These were in part different from each other only in a few fragments and thus displayed a close clonal relation. The results of the present investigation showed that identical or closely related clones seemed to be responsible for the cases of bovine mastitis in the farms investigated and partly responsible for contamination of bulk tank milk.